Lost opportunities for globalisation, digitalisation, and socially sustainable education? Advocating for digital and global Bildung in Swedish upper secondary schools - Bäcke, Maria; Vigmo, Sylvi (Frontiers in Education, 2024)
Our 2022 pilot study indicates that for some multiethnic, multi-abled, and otherwise diverse upper secondary students underlying, often ethnocentric, norms of Swedish education create hurdles in educational contexts. Firstly, their, in the Swedish context, non-normative and often global experiences are not recognised at school. Secondly, topics addressed in the courses they take are primarily focused on topics originating in a Swedish, Nordic, or Western tradition. This may cause tension, as Andreotti and de Souza (2008) indicate: "uncritical reinforcement of notions of the supremacy and universality of 'our' (Western) ways of seeing… can reproduce unequal relations of dialogue and power and undervalue other knowledge systems." In this article, we point to how the making visible of diverse linguistic, digital, and cultural competences can contribute to more sustainable and inclusive classroom contexts and future societies. Curricular policies must take lost opportunities, which we argue are not socially sustainable, into account as a more global and holistic approach when articulating what educational learning is supposed to be about, for, and for whom (Biesta, 2020), and thus integrating learning, digitalisation, and social sustainability.